Vaginal cuff dehiscence is observed in a higher rate after total laparoscopic hysterectomy compared with other types of hysterectomy. (29th October 2018) - Ala‐Nissilä, Seija; Laurikainen, Eija; Mäkinen, Juha; Jokimaa, Varpu
Abstract: Introduction: Recently, it has been suggested that the occurrence of posthysterectomy vaginal cuff dehiscence has increased. Consequently, we evaluated the incidence of vaginal cuff dehiscence after different types of hysterectomies. Our hypothesis is that vaginal cuff dehiscence is more often associated with total laparoscopic hysterectomy (TLH) than other types of uterine removal. Material and methods: A total of 13 645 hysterectomies from 1992 to 2015 were evaluated in the Turku University Hospital district, Finland. The primary outcome was occurrence of vaginal dehiscence after different types of hysterectomy. The hysterectomy and postoperative vaginal dehiscence trends were analyzed as the secondary outcome. In a subanalysis of dehiscence cases, women's characteristics and perioperative vaginal cuff opening and closure techniques were compared between conventional hysterectomies (vaginal, abdominal, and laparoscopic with vaginal closure) and TLH. Results: Altogether, 22 cases of vaginal cuff dehiscence were included. Most cases (n = 15) occurred after TLH (n = 1104), resulting in an incidence of 1.27%. After conventional laparoscopic hysterectomy with vaginal closure (n = 2853), vaginal (n = 4150), and abdominal (n = 5538) hysterectomies, the incidence rates were 0.11%, 0.05%, and 0.02%, respectively. Compared to abdominal hysterectomy, which was associated with the lowest incidence rate, vaginal dehiscence after TLH had an odds ratio (OR) 71.1 (9.34‐541.38, P < 0.001). In the subanalysis of possible underlying factors, the technique of opening of the vaginal cuff with or without electrocoagulation, duration of operation, and occurrence of postoperative infection or hematoma prior to VCD were observed differences between TLH and conventional hysterectomies. Conclusions: Compared with other types of hysterectomies, vaginal dehiscence was observed at the highest rate after TLH. Studies are needed to define if vaginal opening technique contributes to the risk of dehiscence.